The employees and customers’ satisfaction perception on financial performance: A model of service-profit-chain in Jakarta - Rudyanto Rudyanto (Journal of Economics, Business, and Accountancy Ventura, 2014)
The purpose of this study is to examine the impact of the relationship between employee satisfaction and customer satisfaction, and also to examine the impact of both on a hospitality company’s financial performance utilizing service-profit-chain framework as the theoretical base. Specifically, this study explores four major relationships: 1) The direct relationship between customer satisfaction and financial  performance; 2) The direct relationship between employee satisfaction and financial performance; 3) The direct relationship between customer satisfaction and employee satisfaction; and 4) The indirect relationship between employee satisfaction and financial performance. Furthermore, this study examines the mediating role of customer satisfaction on the indirect relationship between employee satisfaction and financial performance. The data were collected from employees, customers and managers of hotels in Jakarta. LISREL 8.8 Structural Equation Modeling (SEM) with a two-step approach was utilized to empirically test the proposed hypotheses and the relationships between the constructs. Findings suggest that while customer satisfaction has  positive significant effect on financial performance, employee satisfaction has no direct significant effect on financial performance. Instead, there is an indirect relationship between employee satisfaction and financial performance, which is mediated by customer satisfaction.